Commuting Time and Sex Ratios in the US - J. Ignacio Gimenez-Nadal; José Alberto Molina; Jorge Velilla (Institute for the Study of Labor (IZA), 2016)
In this paper, we analyze the relationship between potential worker supply, measured through sex ratios, and commuting times in the United States. Using the American Time Use Survey 2003-2014, we analyze the relationship between commuting times and sex ratios by state and age, and show that the proportion of males to females is negatively related to the commuting times of both male and female workers. Furthermore, this result applies to both private and public sector employees, but does not apply to the self-employed. To the extent that employers compensate their workers for their commutes, our results are important for employers. Given the negative effects of commuting on wellbeing and health, our results imply that individuals living in areas with higher sex ratios may have comparatively better health and well-being outcomes than workers living in areas with lower sex ratios.
Keywords: C21; J22; R41; 330; commuting time; sex ratio; ATUS; gender gap; United States